Coopetition in innovation activities and firms' economic performance: An empirical analysis. (24th July 2019) - Pekovic, Sanja; Grolleau, Gilles; Mzoughi, Naoufel
Abstract : We use survey data to test whether it pays to cooperate in innovation activities with rivals (also referred to as coopetition) compared to other cooperative arrangements, notably with non‐rival partners. Applying an ordinary least squares regression to a large sample of French firms ( N  = 2957), we found evidence of a positive and significant relationship between various forms of cooperation (with and without rivals) and firms' economic performance, measured by EBITDA (earnings before interest, taxes, depreciation and amortization). Results show that cooperation with rival and non‐rivals taken together increases economic performance, but that the impact of cooperation with rivals is lower than the impact of cooperation with non‐rivals. Estimation results suggest that reaping the full cooperation benefits is not automatic and requires precision dosing and management.